An alternative index for evaluating AMU and anti-methicillin-resistant Staphylococcus aureus agent use: A study based on the National Database of Health Insurance Claims and Specific Health Checkups data of Japan. Issue 7 (July 2021) - Mita, Yosuke; Inose, Ryo; Goto, Ryota; Kusama, Yoshiki; Koizumi, Ryuji; Yamasaki, Daisuke; Ishikane, Masahiro; Tanabe, Masaki; Ohmagari, Norio; Muraki, Yuichi
Abstract: Introduction: Anti-methicillin-resistant Staphylococcus aureus (MRSA) agents have different doses and administration periods. Thus, it is difficult to evaluate antimicrobial use (AMU) of anti-MRSA agents using defined daily doses per 1000 inhabitants per day (DID) or days of therapy per 1000 inhabitants per day (DOTID). This study aimed to evaluate the relationship between anti-MRSA agent use and resistant bacteria using the number of patients per 1000 inhabitants per day (PID) as an alternative index of AMU. Methods: AMU data for anti-MRSA agents were collected from the National Database of Health Insurance Claims and Specific Health Checkups (NDB) in 2016. The relationship between PID and DID or DOTID was evaluated. The number of patients with MRSA isolated was obtained from Japan Nosocomial Infections Surveillance, and their correlation with PID was analyzed. The rate of anti-MRSA agent use in each prefecture was investigated. Results: PID showed a significant linear relationship with both DID and DOTID (all p < 0.0001). PID was significantly correlated with the number of patients with MRSA isolated. Additionally, the rate of anti-MRSA agent use was markedly different in each region. Conclusions: PID is not affected by doses and administration periods, and thus may be an alternative index for the selective pressure of antibiotics. Evaluating AMU using PID based on NDB data will help in the development of effective antimicrobial resistance measures.